2022
DOI: 10.1002/dta.3383
|View full text |Cite
|
Sign up to set email alerts
|

Presence of higenamine in beetroot containing ‘foodstuffs’ and the implication for WADA‐relevant anti‐doping testing

Abstract: Higenamine is an alkaloid found within plant species including some that are used in traditional Asian and Chinese herbal medicines. Identified as having mixed mode adrenergic receptor activity, higenamine is present within some nutritional supplements marketed for stimulant and/or weight loss. Its inclusion within nutritional supplements can be via its natural presence within botanical ingredients or as a synthetic additive, often added in mg amounts. The World Anti-doping Agency (WADA) prohibited list has co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Leaney et al investigated the potential of beetroot to contribute to higenamine findings in the context of sports drug testing and demonstrated the presence of higenamine in various processed beetroot products up to ca. 300 ng/g 86 . Elimination studies with such products resulted in urinary higenamine levels below 0.1 ng/mL, that is, approximately 100‐fold below the currently applied MRL of 10 ng/mL.…”
Section: β2‐agonists Hormone and Metabolic Modulatorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Leaney et al investigated the potential of beetroot to contribute to higenamine findings in the context of sports drug testing and demonstrated the presence of higenamine in various processed beetroot products up to ca. 300 ng/g 86 . Elimination studies with such products resulted in urinary higenamine levels below 0.1 ng/mL, that is, approximately 100‐fold below the currently applied MRL of 10 ng/mL.…”
Section: β2‐agonists Hormone and Metabolic Modulatorsmentioning
confidence: 96%
“…300 ng/g. 86 Elimination studies with such products resulted in urinary higenamine levels below 0.1 ng/mL, that is, approximately 100-fold below the currently applied MRL of 10 ng/mL.…”
Section: Steroid Profiling In Urine and Bloodmentioning
confidence: 99%
“…Methylated fractions were then subjected to nuclear magnetic resonance spectroscopy (NMR). Therefore, the substances of interest were dissolved and transferred into the NMR tube using 50 μL of deuterated dimethylsulfoxide (DMSO-D 6 ), and 1 H, 1 H, 1 H-COSY, 13 C-1 H-HSQC, and 13 C-1 H-HMBC experiments were conducted utilizing a BRUKER AVANCE NEO 800 MHz NMR spectrometer (Bruker, Karlsruhe, Germany).…”
Section: Higenamine Sulfo-conjugates Synthesis and Structural Charact...mentioning
confidence: 99%
“…[3][4][5][6][7] Higenamine has been described as a key component of a great variety of natural plants such as Nandina domestica, Tinospora crispa, and recently Beta vulgaris. [8][9][10][11][12][13] The content of higenamine in natural plants can vary greatly, prompting numerous studies to investigate whether the consumption of plant extracts or products commonly used in popular medicine can lead to an AAF. In some cases, these studies have demonstrated the risk of unintentional anti-doping rule violations (e.g., Nelumbo nucifera).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the study by Kozhuharov, Ivanov, and Ivanova [11] analyzed 50 studies published between 1996 and June 21, 2021, and found a prevalence of 28% of contamination among food supplements. After this period, in our searches, using the same descriptors and research platforms, we found four more studies [31][32][33][34] whose objective was to evaluate the contamination of sports food supplements.…”
Section: Prevalence Of Contamination Of Food Supplements Their Main C...mentioning
confidence: 99%